Takagi–Sugeno Fuzzy-Based CNF Control Approach Considering a Class of Constrained Nonlinear Systems. Issue 6 (2nd November 2019) - Ebrahimi Mollabashi, H.; Mazinan, A. H.; Hamidi, H.
ABSTRACT: This paper proposes a parallel distributed compensation-based composite nonlinear feedback (CNF) control approach for a class of constrained nonlinear systems, which is described based on Takagi–Sugeno (T-S) fuzzy models with input saturation. By producing invariant sets, the sufficient conditions guarantee the asymptotic stability of the closed-loop system. The presence of input saturation nonlinearity is derived in terms of linear matrix inequality. To the best knowledge of the authors, the research presented here is taken into real consideration as the first attempt to propose a new T-S fuzzy-based CNF control approach. Contrary to the existing CNF outcomes for the linear systems, the proposed one is now applicable to cope with a class of nonlinear systems. In a word, the present CNF control approach comprises two nonlinear parts. It is to note that the first term assures the stability of the closed-loop nonlinear system and provides a fast convergence response, as long as the second term reduces the overshoot of the response, correspondingly. In one such case, the overall CNF control approach satisfies the predefined input saturation, as well. In the sequel, in order to illustrate the merits of the proposed control approach, the continuous stirred tank reactors and the electromagnetic suspension system are chosen to verify the investigated results in comparison with those obtained from the existing results.